2015
DOI: 10.1371/journal.pone.0143071
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Virus-Like Particle Based Vaccine Platform Displaying the Placental Malaria Antigen VAR2CSA

Abstract: Placental malaria caused by Plasmodium falciparum is a major cause of mortality and severe morbidity. Clinical testing of a soluble protein-based vaccine containing the parasite ligand, VAR2CSA, has been initiated. VAR2CSA binds to the human receptor chondroitin sulphate A (CSA) and is responsible for sequestration of Plasmodium falciparum infected erythrocytes in the placenta. It is imperative that a vaccine against malaria in pregnancy, if administered to women before they become pregnant, can induce a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
0
46
0
Order By: Relevance
“…This, in turn, can be utilized to fuse the antigen with monovalent streptavidin without disrupting the assembly of VLPs and their activity. [85]…”
Section: Applications In Nanoscale Delivery Systemsmentioning
confidence: 99%
“…This, in turn, can be utilized to fuse the antigen with monovalent streptavidin without disrupting the assembly of VLPs and their activity. [85]…”
Section: Applications In Nanoscale Delivery Systemsmentioning
confidence: 99%
“…Sortase-mediated conjugation allows for site-directed ligation of cargoes (including peptides and small molecules) bearing a specific amino acid tag (LPETG) to VLPs that have been modified to include a target sequence (a stretch of glycine residues) [21]. Similarly, VLPs have been engineered to display poly-histidine stretches (for non-covalent conjugation to antigens with NTA-Ni 2+ moiety) [22], methionine analogues for use with click chemistry [23], or other proteins or tags that allow for non-covalent [24,25] or covalent [26] interactions. These techniques allow VLPs to display diverse antigens, including peptides, full-length proteins, carbohydrates, and other small molecules.…”
Section: Engineering Vlps To Display Diverse Antigensmentioning
confidence: 99%
“…HbsAg VLPs) leads to induction of strong and durable antibody responses [18, 19]. Recent studies have shown that vaccine antigens presented on VLP platforms effectively induce high titred antibody responses against poorly immunogenic antigens [20, 21]. One of these studies utilizes a split-intein (SpyTag/SpyCatcher) conjugation system to covalently attach antigens on the surface of rigid Acinetobacter phage AP205 VLPs.…”
Section: Introductionmentioning
confidence: 99%